ELEMENTS AND SUBJECTS OF THE PROOF PROCESS IN CRIMINAL PROCEEDINGS IN THE CONDITIONS OF THE LEGAL REGIME OF MARTYR STATE (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that the key elements of the evidentiary process include: identification and collection of evidence, its initial and subsequent verification, assessment of the admissibility, relevance, reliability and sufficiency of each piece of evidence both independently and in the system of all collected materials, as well as their use when making relevant procedural decisions. It is found that these issues acquire particular relevance in the legal regime of martial law, when the possibilities of rapid response, ensuring procedural guarantees and the balance of rights and obligations of the participants in the process are subject to additional challenges. It has been established that the subject composition of the evidentiary process is divided into two main groups: subjects who carry out the evidentiary process (investigator, inquirer, prosecutor, investigating judge, court), and subjects who contribute to the evidentiary process or have an interest in it (defense party, victim, representative of a legal entity, witnesses, experts, specialists, translators). It has been noted that each of these subjects performs a unique function that ensures the systematic and complete collection, research, evaluation and use of evidence. It has been emphasized that special attention should be paid to ensuring the balance of procedural rights, in particular, avoiding the erroneous transfer of the burden of proof to the defense or replacing the presumption of innocence with its opposite. It has been established that the active participation of both parties in the adversarial process, especially in conditions of martial law, makes it possible to ensure a fair trial and guarantee real protection of human rights. It is emphasized that the effective organization and implementation of the evidentiary process with the participation of all subjects and subject to strict adherence to the elements of the evidentiary process is the key to impartial and fair justice in criminal proceedings, regardless of the action of martial law.
Keywords: evidence; evidentiary process; criminal proceedings; criminal procedural evidence; criminal procedural legislation; judicial practice; elements; subjects of evidence; subject composition; martial law